COST ESTIMATE OF ECONOMIC DISBENEFIT IN BUILDING MATERIALS PRODUCTION AND USE - Nikolay B. Svechnikov (Advanced Engineering Research, 2011)
The concept of damage ensuing in the production and use of the building materials, and during damaging contacting throughout the life cycle of the building components is described. Calculations of the emissions of harmful substances, in particular carbon dioxide, are resulted. The damage evaluation is given in value terms.